Citizenship beyond the state - Hoffman, John, 1944- (SAGE, 2004)
Citizenship Beyond the State is a critical introduction to the concept of citizenship: it challenges the notion that citizenship has to be defined as membership of a state (a notion implicit in Derek Heater's book, and only touched on in Keith Faulks' earlier work).